'We were all looking at them quite critically': collaborative reflection on a university-based coach education program. Issue 2 (4th March 2021) - Dixon, Martin; Lee, Chris; Corrigan, Craig
ABSTRACT: Despite the potential to enhance learning in higher education, collaborative reflection in practical settings has received limited attention. This study investigated collaborative reflection within peer coaching assessments on a university-based coach education program. Data were collected through focus groups with undergraduate sports coaching students and individual interviews with module instructors. Thematic analysis revealed three main themes and six sub-themes as follows: reflective processes (evaluating peers' experiences, collaboration through shared knowledge); social support (practical support, emotional support); and engagement (task engagement, pressure of assessment). Evaluating peer coaching performance through observation, participation, and discussion enhanced students' awareness of their own coaching practice. Findings highlight a tendency for students to exchange knowledge informally and several barriers to collective reflection within formal practical settings. Students provided social support to help peers manage the demands of practical coaching assessments. Instructors' perspectives supported and challenged the student data, culminating in recommendations to enhance collaborative reflection within and beyond a module of study.